Effect of Electronic Taxation on Revenue Productivity in Nigeria - Olaoye, Clement Olatunji; Ayeni-Agbaje, A. R.; Adebayo, Isaac Adesodun; Adesodun, Ruth Bosede (Archives of Business Research, 2022)
This study investigated the effect of electronic taxation on revenue productivity in Nigeria. Specifically, the study examined the difference between revenue productivity before and during e-taxation, effect of e-taxation adoption on revenue productivity and tax to GDP ratio in Nigeria. The study employed secondary data covering the period 2000-2017. Data were analyzed using, trend analysis, independent t-test and ordinary least regression estimator. Result revealed that there is significant difference between revenue productivity in the pre and post e-taxation adoption and that the revenue productivity is higher at the post adoption. Also, this study showed that e-taxation has significant positive effect on actual tax revenue and tax to GDP ratio in Nigeria with coefficient of 2083.034 (p<0.05) and 1.017351 (p> 0.05). The study concluded that there is a substantial difference between the level of revenue productivity of the pre and post adoption of electronic taxation, and established that the effect of adoption of electronic taxation on actual tax revenue generation in the country is positive and significant, though such impact does not hold a substantial ground in the discourse of the ratio of tax revenue to the level of gross domestic product in the country.